P-block element modulated 1 T phase MoS2 with Ru lattice grafting for high-performance Li | |O2 batteries - Peng Wang; Danyang Zhao; Peng Zhang; Xiaobin Hui; Zhiwei Zhang; Rutao Wang; Chengxiang Wang; Xiaoli Ge; Xiaojing Liu; Yuguang C. Li; Longwei Yin (Nature Communications)
Abstract The metallic phase MoS2 (1T-MoS2) supported metal-nanocatalyst is an appealing material system for accelerating the redox kinetics of non-aqueous Li | |O2 batteries. However, the drawbacks associated with the surface orbital steric effect and the internal electron coupling results in a detrimental effect for the stability of 1T-MoS2, especially for the interface charge transfer. This makes it difficult to incorporate guest metal nanoparticles without compromising the 1 T phase support. To circumvent these issues, here we propose a p-block element (In-O) doping strategy to stabilize the 1 T phase MoS2 by moderating the surface orbital steric effect and strengthening the internal chemical bonding, and thus for the epitaxial Ru nanocatalyst graft on the stabilized 1T-MoS2 for Li | |O2 batteries. The experimental and theoretical analyzes indicate that the In-O-MoS2@Ru enhances the O2 dissociation and facilitates the adsorption of LiO2 intermediates. This effect promotes the growth of weakly crystalline Li2O2 films during oxygen reduction reaction, which can be more easily decomposed during the oxygen evolution reaction, thereby enhancing the bifunctional-catalytic kinetics. When employed at the positive electrode for non-aqueous Li | |O2 batteries, In-O-MoS2@Ru shows an overpotential of 0.37 V and a cycling life of 284 cycles at 200 mA g−1 with a final discharge specific capacity of 1000 mAh g−1 at 25 °C.